2021
DOI: 10.1111/ggi.14254
|View full text |Cite
|
Sign up to set email alerts
|

Short physical performance battery score and driving a car are independent factors associated with life‐space activities in older adults with cardiovascular disease

Abstract: Decreased use of life spaces, as reflected in decreased Life-Space Assessment (LSA) scores, is associated with poor prognosis in older adults. The purpose of this study was to examine factors affecting the extent of life-space activities in older adults with cardiovascular disease.Methods: We carried out a prospective observational study in 98 older adults (minimum age 65 years; mean age 79.5 AE 7.4 years) who were admitted to our hospital due to cardiovascular disease. Once their medical condition was stable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In our population, 87.7% of the subjects were admitted to our hospital due to worsening heart failure ( Table 1 ). In our previous cross-sectional study, we found that in addition to an assessment of clinical cardiac function, an assessment of motor function and social factors might also be important to understand the complete context of life-space activity in older adults with CVD [ 24 ]. The present study was a medium-term longitudinal study to elucidate the relationship between LSA and prognosis in a similar population, and the Cox proportional hazards analysis revealed that life-space activities are independently associated with cardiovascular events after adjusting for age and disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our population, 87.7% of the subjects were admitted to our hospital due to worsening heart failure ( Table 1 ). In our previous cross-sectional study, we found that in addition to an assessment of clinical cardiac function, an assessment of motor function and social factors might also be important to understand the complete context of life-space activity in older adults with CVD [ 24 ]. The present study was a medium-term longitudinal study to elucidate the relationship between LSA and prognosis in a similar population, and the Cox proportional hazards analysis revealed that life-space activities are independently associated with cardiovascular events after adjusting for age and disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The present study further demonstrates the importance of factors other than cardiac function and BNP in the prognosis of older adults with CVD. LSA is reported to be associated not only with BNP but also with physical function, physical activity, depression, cognitive function, and social factors [ 24 , 27 ]. LSA is associated with multiple prognostic factors for CVD.…”
Section: Discussionmentioning
confidence: 99%